2004
DOI: 10.2337/diaspect.17.4.244
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Testing in Diabetes Management: What Role Does It Play?

Abstract: Diabetes is a multisystem disease requiring complex management provided by a variety health care professionals (HCPs). Comprehensive care of patients with diabetes requires frequent testing of hemoglobin A1c (A1C),and research indicates that use of point-of-care testing (POCT) can affect patients' A1C results in the shortterm. The purpose of this qualitative study was to explore the ideas, opinions, and expectations of HCPs and patients with diabetes about the potential role of POCT, including its impact on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…37 Subjective perceptions of health-care providers and patients regarding POC testing impact on diabetes management were examined in a qualitative study based on in-depth interviews. 26 All interviewees agreed that an improved opportunity for treatment adoption provided by the rapid availability of HbA1c results was an important advantage of POC testing. A positive reception of HbA1c testing at POC by both patients and physicians was reported.…”
Section: A Improved Diabetes Management/treatment Adaptationmentioning
confidence: 99%
“…37 Subjective perceptions of health-care providers and patients regarding POC testing impact on diabetes management were examined in a qualitative study based on in-depth interviews. 26 All interviewees agreed that an improved opportunity for treatment adoption provided by the rapid availability of HbA1c results was an important advantage of POC testing. A positive reception of HbA1c testing at POC by both patients and physicians was reported.…”
Section: A Improved Diabetes Management/treatment Adaptationmentioning
confidence: 99%
“…A key factor with managing diabetes is the point-of-care testing device. Previous research has focused primarily on the quality of point-of-care devices compared to laboratory testing [4,7]. This research takes it a step further by not only studying the devices' reliability, but also what role these devices play in the management of diabetes by elderly and if the elderly are satisfied with the current devices.…”
Section: Discussion and Future Workmentioning
confidence: 98%
“…More important was to see what role point-of-care testing plays in that management and what can be improved about those devices in the eyes of the elderly. There is already some extensive amount of research done on point-of-care testing in combination with diabetes [4] and diabetes management [5,6]. Research has found that there are two themes that play a central role in POCT and diabetes.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations